PENGARUH KUALITAS LAYANAN, PERSEPSI NILAI DAN KEPERCAYAAN TERHADAP KEPUASAN DAN LOYALITAS PENGGUNA LAYANAN MOBILE BANKING - Heri Setiawan (University of Merdeka Malang, 2016)
This study aims to determine the determinant of customer satisfaction and loyalty implications for users of mobile banking. This study used Structural Equation Modeling (SEM) to test the hypotheses of the study and use the software AMOS 5.0 and SPSS 20.0. The population in this study are the mobile banking users in seven banks in Palembang City; Bank Mandiri, Bank BNI, Bank BRI, Bank Danamon, BCA, and Bank Permata. The research sample consist of 250 respondents to the provisions of the election to the mobile banking users. The results showed that the service quality, perceived value, trust and customer satisfaction has a strong effect on customer loyalty. Service quality have significant effect on consumer satisfaction. Perceived of value have significant effect on customer satisfaction. Trust have significant effect on consumer satisfaction. Service quality have significant effect on customer loyalty. Trust have significant effect on customer loyalty. Customer satisfaction have significant effect on customer loyalty. Banks should build strong relationships with customers and provide better service quality to reduce the behavior of customers to switch to another bank service.